Pharmacological treatments in alcohol use disorder and risk of alcohol-related hospitalizations: A Register Study - Bach, Patrick; Franck, Johan; Hällgren, Jonas; Widing, Härje; Gissler, Mika; Westman, Jeanette (Acta psychiatrica Scandinavica, 2025)
Objectives Despite the high prevalence of alcohol use disorder (AUD), only a minority of patients receive recommended pharmacological treatments, possibly owing to uncertainty about the real-world effectiveness of these medications. Here, we analyzed nationwide, register-based data to investigate the association between approved AUD medications (naltrexone, acamprosate, disulfiram, and nalmefene) and the risk of alcohol-related hospitalizations among individuals with AUD. Methods People aged 18-64 with a registered first-time diagnosis of AUD between 2009 and 2019 (N = 93,727) were identified from the Swedish National Patient Register. Cox regression models were used to analyze the association between AUD medication exposure and the risk of alcohol-related hospitalizations. Results Exposure to naltrexone (hazard ratio [HR] = 0.80; 95% confidence interval [CI] = 0.73-0.87) or disulfiram (HR = 0.83, 95% CI = 0.79-0.88) as monotherapy, or a combination of naltrexone/disulfiram (HR = 0.68, 95% CI = 0.49-0.96), or disulfiram/acamprosate (HR = 0.57 95% CI = 0.44-0.74) was significantly associated with a lower risk of alcohol-related hospitalizations compared to periods without exposure to any of these medications. In contrast, no significant associations were observed for acamprosate, nalmefene, or the combination of acamprosate/naltrexone. Sensitivity analyses in individuals with severe AUD and stratified subgroup analyses by different socioeconomic groups confirmed the robustness of the results. Conclusion Results indicate a significant association between disulfiram and naltrexone monotherapy, as well as the combination of disulfiram with naltrexone or acamprosate, with a lower risk of alcohol-related hospitalizations among individuals with AUD. Low prescription rates suggest that AUD medications are currently underutilized. Increasing the availability of these medications for individuals with AUD could help reduce alcohol-related hospitalizations.